Judge-Jury Interaction in Deliberation: Enhancement or Obstruction of Independent Jury Decision-Making? - Jae-Hyup Lee; Jisuk Woo (Oñati Socio-Legal Series)
In the Korean jury system, jurors deliberate without interference of anyone, except when they cannot reach a unanimous verdict, in which case they must hear the judge’s opinion. If jurors convict the defendant, they also deliberate with the judge on sentencing and provide their opinions. This unique feature of the Korean jury system provides rare opportunities to examine the interaction of the lay people and judges in deliberation. Through direct observation and the content analysis of the shadow jury deliberations on actual cases in Korea, we will examine whether the judge’s intervention was helpful in jury decision-making or hampers the independent judgment of the jury. The result shows the collaborative deliberation amongst jurors and judges in sentencing, and in some cases in conviction, will mutually benefit both. In turn, jurors will retain the credibility of the judiciary while the judges will reflect upon their decisions in accordance with the legal consciousness of the lay people. En el sistema de jurados de Corea, los miembros del jurado deliberan sin interferencia de nadie, excepto cuando no pueden llegar a un veredicto unánime, en cuyo caso deben escuchar la opinión del juez. Si los miembros del jurado condenan al acusado, también deliberan con el juez a la hora de dictar sentencia y expresan sus opiniones. Esta característica única del sistema de jurados de Corea ofrece pocas oportunidades para examinar la interacción del jurado popular y los jueces durante su deliberación. A través de la observación directa y el análisis del contenido de las deliberaciones del jurado en la sombra sobre casos reales en Corea, se analizará si la intervención del juez fue útil en la toma de decisiones del jurado o dificulta su independencia de criterio. El resultado demuestra que la deliberación entre los miembros del jurado y los jueces a la hora de dictar sentencia, y en algunos casos al declarar culpable al acusado, beneficia a ambos. A su vez, los miembros del jurado conservan la credibilidad del poder judicial, mientras que los jueces van a dictar sentencia teniendo en cuenta la conciencia jurídica del tribunal popular. DOWNLOAD THIS PAPER FROM SSRN: http://ssrn.com/abstract=2606614